Association between weight loss and clinical-pathologic factors in oncological patients in chemotherapy treatment: a longitudinal study (Acta Scientiarum. Health Sciences, 2019)
The present study aimed to evaluate the nutritional state and WL of individuals with cancer. Is a longitudinal observational study was performed with patients assisted in the oncological ambulatory. Sample was composed of 402 patients, with an average of 58.46±13.60 years old, 56.5% women and the majority elderly (51.74%). Regarding tumor localization, 12.9% were found in the head and neck, 22.6% in mamas, 10.2% in the lungs, 29.4% in the gastrointestinal tract (GI tract) and 29.4% in other body parts. A gradual fall of nutritional state in relation to BMI was observed, and the patients were advancing to malnutrition. When severe and not severe WL were correlated, a statistical difference was demonstrated regarding age, current and habitual weight, as well as the corresponding BMI (p